On the multivariate characteristic functions - Bikelis, A. (Lithuanian Mathematical Journal, 1968)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: А. Бикялис. О многомерных характеристических функциях A. Bikelis. Apie daugiamates charakteringas funkcijas